Folk culture resources as a component of tourism space - Mokras-Grabowska, Justyna (Turyzm/Tourism, 2013)
The paper concerns folk tourism – describes the mutual relations between folk culture and tourism and the main mechanisms of the commercialization of cultural heritage. Moreover it locates folk culture resources in tourism space and includes hospitality.